Notebook [29, Spring 1992] - Leier, Mark (James Mark) (Labour / Le Travail, 1992)
Takes note of forthcoming conferences and the continuation of the Marx-Engels Gesamtausgabe with the signing of an agreement between the Amsterdam-based International Marx-Engels Foundation and the Conference of German Academies of the Sciences.
Keywords: CONFERENCES & conventions; Canada; LABOR – Congresses; MICHIGAN; MINNESOTA; WORKSHOPS (Adult education)